PERBANDINGAN KADAR IL-6 KERADANGAN HARI KE-3 PASKA PENCABUTAN GIGI PADA RATTUS NOVERGICUS BETINA MENOPAUSE: Indonesia - Parmasari, Wahyuni Dyah; Rianti, Emilia Devi Dwi (Fakultas Kedokteran Gigi UB, 2025)
Background The wound healing process after tooth extraction includes inflammation, granulation tissue formation, intracellular matrix deposition and tissue remodeling. IL-6 acts as a biomarker of the inflammatory process. In old age, especially women, the menopause process cannot be avoided and at that age the need for tooth extraction treatment is quite high. If there is failure in the wound healing process, in this case the inflammation process will prolong, increasing the probability of infection, one of which is alveolar osteitis. The menopause process affects estrogen levels in the blood, so the formation of collagen as the main ingredient for tissue regeneration is reduced, and IL-6 can increase during times of inflammation, especially the chronic phase. Objectives This study compared inflammatory IL-6 levels using the ELISA method in menopausal and non-menopausal mice. Methode In this study there were 10 rats (rattus novergicus) which were then grouped into 2 groups, namely control and treatment. Control group where no oophorectomy was performed (non-menopausal) while the treatment was carried out by oophorectomy (menopause). Then 1 month later, the tooth was extracted and observed on the 3rd day after extraction. Result showed that the average IL6 level in the control group was 0.0868 (ng/L) and in the treatment group was 0.1912 (ng/L). then continued with the Mann Whitney non-parametric statistical test with a significance level of 95% (p<0.05). Conclusions There was a significant difference between the treatment and control groups, where IL-6 levels in the menopausal group were higher than in the non-menopausal group.